2020
DOI: 10.3889/oamjms.2020.5229
|View full text |Cite
|
Sign up to set email alerts
|

Association of Gender, Triglyceride/HDL Ratio, and Physical Activity of Obese Adolescents in Makassar

Abstract: BACKGROUND: Obesity may cause the increase of triglyceride and decrease of high-density lipoprotein (HDL) levels. Triglyceride/HDL ratio is associated with metabolic disorders. Physical activity is one of the important aspects in preventing obesity. Gender is known to have a relationship with these factors, but it has been inconsistent. AIM: This study aimed to evaluate the relationship between sex and triglycerides, levels of HDL, triglycerides/HDL ratio, and physical activity of obese adolescents in Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Although high level of blood triglyceride was a determinant of T2DM in both genders in our study, the results showed that the prevalence of high blood triglyceride level was significantly higher in men than women (p <0.001). A study on adolescents showed that the high levels of triglyceride were more common in boys than girls [ 43 ]. Differences in blood triglyceride levels can be attributed to different eating patterns between genders.…”
Section: Discussionmentioning
confidence: 99%
“…Although high level of blood triglyceride was a determinant of T2DM in both genders in our study, the results showed that the prevalence of high blood triglyceride level was significantly higher in men than women (p <0.001). A study on adolescents showed that the high levels of triglyceride were more common in boys than girls [ 43 ]. Differences in blood triglyceride levels can be attributed to different eating patterns between genders.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens upregulate the synthesis, release and activity of protective agent on endothelial, and suppress the expression of pathogenic agents by endothelium via estrogen receptor (ER), Er α and Er β , on vasculature [ 36 ], while androgens are suspected to be proatherogenic [ 37 ]. Moreover, estrogen is able to reduce the fat accumulation in women [ 38 ] and showed that its level is higher than men/boys at any age [ 37 ]. The in vitro study exhibited that estrogen inhibits smooth muscles by activating potassium efflux and inhibiting calcium influx.…”
Section: Discussionmentioning
confidence: 99%